A case study on turnover of operational staff at multinational company in Kuantan, Pahang and its effect to the productivity = kajian kepuasan kerja dan komitmen organisasi serta kesannya terhadap kecenderungan / niat berhenti kerja di kalangan staf bahagian operasi syarikat multinasional di Kuantan, Pahang - Ahmad Fazullah, Mohd Zainal Abidin; Imaduddin, Abidin; Jamal Rizal, Razali; Razak, Munira Abdul; Husna, Hashim; Ngah, Ezihaslinda; Ghani, Airin Abdul (2012)
This study aims to identify the factors that influence the turnover phenomenon among the operational staffs of multinational companies in Kuantan Pahang. This study focuses on assessing the facets of job satisfaction which are People on Your Present Job, Work on Present Job, Pay, Opportunities for Promotion & Supervision, Job in General, organizational commitment and its effect on the tendency to leave their job and organization. This study uses survey design and multivariate analysis. A total of 79 personnel of of full-time employees (operational staffs division) at two multinational companies in Kuantan Pahang were selected as subject by using probability sampling-simple random sampling technique. Data obtained through a survey demographics profile and four instruments which are Job Descriptive Index & Job in General (JDI & JIG), Organizational Commitment Questionnaires (OCQ) and Intent to Quit (ITQ). Data was analyzed based on t-test, Analysis of Variance (ANOV A) and Structural Equation Modeling (SEM)-Partial Least Squares (PLS) statistical techniques by using SPSS 16.0 and SmartPLS 2.0 M3. Findings indicate that there was significant relationship between demographic variables with the components of job satisfaction, commitment to the organization and the tendency to leave the organization. This study also analyzes the significance of the measurement model and structural model that includes the idea of job satisfaction, commitment to the organization and the tendency to leave the organization. This study involves measurement and structural model that includes the dimensions of job satisfaction, organizational commitment and the tendency to leave the organization especially among operational division staffs. Thus, concepts and theories used in this study can be developed for cross-cultural and local context, particularly for organizations in Malaysia. In addition, it becomes the basis for further studies to various factors that increase job satisfaction, organizational commitment thus reducing the phenomenon of turnover among employees. Based on the findings, implications and recommendations for future research are also discussed.